1988
DOI: 10.1038/ki.1988.51
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hyperlipidemia reduces glomerular injury in obese Zucker rats

Abstract: Hyperlipidemic obese Zucker rats develop albuminuria and spontaneous focal glomerulosclerosis (FGS) at an early age, despite normal glomerular capillary pressures and nephron plasma flows. To investigate the role of abnormal lipid metabolism in the pathogenesis of FGS, pharmacologic agents were used to reduce serum lipids in male, obese Zucker rats. Eight rats were treated from 8 to 40 weeks of age with the cholesterol synthesis inhibitor, mevinolin (group I). A separate group of seven obese rats was treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
180
1
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(191 citation statements)
references
References 19 publications
7
180
1
3
Order By: Relevance
“…During the second 6 weeks the patients received a placebo (twice a day) and information collected during this period served as baseline data. Then the patients were randomly assigned to a 6 weeks' treatment period with simvastatin 20 mg twice a day or cholestyramine 8 …”
Section: Study Design and Laboratory Methodsmentioning
confidence: 99%
“…During the second 6 weeks the patients received a placebo (twice a day) and information collected during this period served as baseline data. Then the patients were randomly assigned to a 6 weeks' treatment period with simvastatin 20 mg twice a day or cholestyramine 8 …”
Section: Study Design and Laboratory Methodsmentioning
confidence: 99%
“…Hyperlipidaemia has been shown to play a role in initiation and progression of glomerular injury in animal models [38,39]. A positive correlation has been found between serum cholesterol and rate of decline in glomerular filtration rate in IDDM patients with diabetic nephropathy [17] and in proteinuric non-diabetic patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown development and progression of kidney damage in the setting of hyperlipidemia with increased glomerulosclerosis and tubulointerstitial damage (3)(4)(5)(6). In epidemiologic studies, the presence of dyslipidemia was associated with a higher risk of development of incident CKD in the general population (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%